ANALISIS SIKAP DAN PERILAKU PETANI DALAM MENABUNG DI BANK BRI SIMPAN PINJAM CABANG UJUNG BATU - Freddi Jimmi S; Ahmad Rifai; Didi Muwardi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this study was toanalyze attitude and behavior of farmer in saving money in the saving and loan BRI branch stone tip.analyze relationship with the farmer attitude saving behavior in the saving and loans Bank BRI branch of Ujung Batu . The data used primary data and the sampling technique is purposive sampling combined with accidental sampling . Based on the result of this study concluded that. Overall attitude of farmerto save on BRI Ujung Batu categorized quite good . Cognitive attitude of farmer showed that cognitive attitude of farmer had an average of 3,31 by category quite well . Affective attitude of farmer had an average of 3,33 by category quite well . Conative attitude of farmer had an average of 3,32 by category quite well. The behavior of farmer in saving in BRI Ujung Batu categorized quite good . Farmer saving behavior by cultural factor have an average 3,25 by category quite well . based on social factor have on average 3,32 by category quite well . personal factorhad an average of 3,23 by category quite well and psychologi factor have an average of 3,33 by category quite well. The attitude of farmer have a real positive relationship with saving behavior in BRI Ujung Batu . With the value of rs = 0669 . this indicate that this relationship is the category of strong and have a positive relationship real. . Keywords: Saving at Bank, Behaviour,Tricomponent Attitude Model